S111 Differences in characteristics and outcomes in systemic sclerosis-associated and idiopathic pulmonary arterial hypertension. (15th November 2016) - Ramjug, S; Hussain, N; Hurdman, J; Billings, C; Elliot, CA; Kiely, DG; Sabroe, I; Rajaram, S; Swift, AJ; Condliffe, R
Abstract : Background: Previous studies have demonstrated survival in systemic sclerosis (SSc)-associated pulmonary arterial hypertension (SSc-PAH) to be worse than in idiopathic pulmonary arterial hypertension (IPAH). Possible explanations include age, differences in the underlying pulmonary vasculopathy and the ability of the right ventricle to compensate for the increased afterload. 1 We investigated differences between these conditions by comparing demographic, haemodynamic and cardiac magnetic resonance imaging (MRI) characteristics and outcomes in a large cohort of incident, treatment-naive patients. Methods: 183 patients with IPAH and 192 patients with SSc-PAH were identified from departmental databases including the ASPIRE registry. 2 Sub-group analysis in 83 patients who had undergone cardiac MRI within 14 days of right heart catheterisation was performed. Results: Median survival in IPAH was 7.8 years and in SSc-PAH was 3 years (p < 0.001). Patients with SSc-PAH were older with milder pulmonary haemodynamics but lower gas transfer (DLCO ). Independent prognostic factors at multivariate Cox regression analysis were age, presence of systemic sclerosis, DLCO, pulmonary artery saturation and stroke volume. For a given resistance (R), pulmonary arterial compliance (C) was reduced (lower RC) in SSc-PAH (Figure ). The relationship between mean pulmonary arterial pressure (mPAP) and systolic pulmonary arterial pressure (sPAP) in IPAH was identical to that previously reported (mPAP = 0.61 sPAP + 2 mmHg). The relationship in SSc-PAH was found to be: mPAP = 0.58 sPAP + 2 mmHg (p-value for difference with IPAH = 0.095). There was no significant difference in compensatory right ventricular hypertrophy when corrected for afterload while the correlation between ventricular mass index (right ventricular mass/left ventricular mass) and pulmonary vascular resistance was stronger in SSc-PAH. Conclusion: The reasons for poorer outcomes in SSc-PAH are likely to be multifactorial including, but not limited to, older age, increased pulmonary arterial stiffness and reduced gas transfer. References: Condliffe R, Howard LS. Connective tissue disease-associated pulmonary arterial hypertension. F1000 Prime Rep . 2015;7 :06. Hurdman J, Condliffe R, Elliot CA, et al . ASPIRE registry: assessing the spectrum of pulmonary hypertension Identified at a REferral centre. Eur Respir J . 2012;39 (4):945–955.